Antonio Francés‐Monerris. Issue 50 (28th October 2021) - Unknown
Abstract : " My motto is perhaps it is not impossible, but no one has tried before with what we know now … I chose chemistry as a career because I love to understand the nature and structure of matter and the processes taking place at the microscopic scale. … " Find out more about Antonio Francés‐Monerris in his Introducing … Profile.